Optimalisasi Potensi Lokal Isi Biji Karet Menjadi Produk Makanan Ringan Yang Bernilai Jual Untuk Meningkatkan UMKM Di Desa Battu Winangun - Yudistira, Kelvin; Wahyuda, Dimas Ari; Arzanti, Zabira; Viana, Isya Bella Nurulia; Nova, Gitta Destalya Adrian (Universitas Negeri Gorontalo, 2026)
Desa Battu Winangun has natural resource potential in the form of rubber seeds which so far have not been utilized optimally and tend to become plantation waste. In fact, rubber seeds have fairly good nutritional content and have the potential to be processed into snack products with market value if they go through proper and safe processing. This activity aims to optimize the utilization of rubber seeds as snack products while also increasing the capacity and independence of Micro, Small, and Medium Enterprises (MSMEs) in Desa Battu Winangun. The methods used include observation of village potential, socialization, training on processing rubber seeds into chips (Kacang), production assistance, and the introduction of packaging and product marketing strategies. The results of the activity show that rubber seeds can be processed into Kacang with a savory taste, crunchy texture, and are acceptable to the community. In addition, this activity increases the knowledge, skills, and interest of the community in developing businesses based on local potential. Optimizing rubber seeds is expected to become a new, sustainable alternative business and contribute to increasing MSME income and the economy of Desa Battu Winangun.